IMPLEMENTASI AKAD PEMBIAYAAN DI KSPPS BMT AL-ITTIFAQIAH INDRALAYA DALAM TINJAUAN FATWA DEWAN SYARIAH NASIONAL - Darsi Ahmadan; Melinda Novayanti (LA RIBA: Jurnal Perbankan Syariah, 2022)
This research was conducted to find out how the implementation of murabahah and ijarah financing contracts at BMT al-ittifaqiah and their suitability with the fatwa of the national sharia council (DSN). The research method in this study is a qualitative method. The data in this study used primary data through interviews and secondary data through literature studies. The data analysis technique used is data reduction to summarize data from the field and data display for data presentation. The results in the study stated that: (1) Implementation of muraba??hah and ijarah contracts at BMT Al-Ittifaqiah Indralaya Ogan Ilir South Sumatra has implemented product operational standards that have been regulated by OJK in the established regulations, and (2) Implementation of muraba??hah and ijarah contracts at BMT Al -Ittifaqiah Indralaya Ogan Ilir South Sumatra has complied with the DSN-MUI fatwa NO.04/DSN-MUI/IV/2000 regarding murabah??ah and DSN-MUI fatwa NO09/DSN-MUI/VI/2000 concerning ijarah contracts, looking at the mechanism of the procedure for implementing the contract at BMT Al-Ittifaqiah Indralaya Ogan Ilir, South Sumatra.